Effects of Hf and Zr Additions on Microstructure, Phase Components and Martensitic Transformation Temperatures of Ni3Ta High-Temperature Shape Memory Alloys - Yildiz, Koksal (Springer, 2023)
Effects of Hf and Zr additions on microstructure, phase components, structural properties, transformation temperatures and damping capacity of Ni3Ta high-temperature SMA were studied via SEM/EDX, XRD, DSC and DMA measurements. Microstructural investigations showed that the microstructure of Ni3Ta contained the Ni8Ta precipitate, intergranular cracks and large-sized voids. Microstructures of Ni74.1Ta25Hf0.9 and Ni74.1Ta25Zr0.9 (at.%) alloys, on the other hand, consisted of micro-sized (NiTa2)-based precipitates and large-sized (Ni2Ta)-based phase regions located along grain boundaries. In addition, eutectic fcc(Ni) + (NiTa2) phase mixture regions were displayed in the surface regions of Ni74.1Ta25Hf0.9 and Ni74.1Ta25Zr0.9 alloys in bulk form. DSC analysis revealed that transformation temperatures of the Ni3Ta were altered by the additions of Hf and Zr, resulting in narrowing transformation hysteresis (A(f)-M-s) values of the alloys. XRD results demonstrated that there were significant changes in both position and intensities of the characteristic diffraction peaks of the Ni3Ta alloy with the additions of Hf and Zr. DMA analysis indicated that maximum damping capacity was found to be 0.101 for the Ni3Ta alloy. However, it was observed that Hf and Zr additions to the alloy caused reducing in their damping capacity to 0.049 and 0.043, respectively.
Keywords: damping; hysteresis; high-temperature SMA; martensite; Ni3Ta